Pengaruh Konsentrasi Air Kelapa Muda dan Madu dalam NaCl Fisiologis terhadap Motilitas dan Lama Hidup Spermatozoa Ikan Patin (Pangasius pangasius) [The Effect of Concentration Young Coconut Water and Honey in 0,9% Sodium Chloride to Motility and Life Time Catfish (Pangasius pangasius) Spermatozoa] - Laksmi Sulmartiwi; Eka Ainurrohmah; A. Shofy Mubarak (Jurnal Ilmiah Perikanan dan Kelautan, 2011)
Abstract Ability nature maturation of catfish just one time a year at early rainy season (November-March) and nature seed population was down because catching, so to solve the probleme is storage of catfish spermatozoa and can used as need. Young coconut water and honey as thinner in storage catfish spermatozoa content glucose and fructose result ATP as energy resources. Destination of this study to know effect of young coconut water and honey to catfish spermatozoa motility and live time in storage process. Study method is experiment with Completely Randomization Design as experimental design. With different treatment young coconut water is A (0%), B (19,4%), C (39,4%), D (59,4%), E (79,4%) and F (99,4%), and add 0,6% honey at every treatment. Save the treatment at 5-7°C for 36 hours with checked every 4 hours. Data analyzed with Anova and continued by Duncan's Multiple Range Test. Result this study shown used young coconut water with different concentration is not different significant at motility but different significant at live time catfish spermatozoa. Young coconut water with concentration 99,4% and honey 0,6% influence at catfish spermatozoa live time.